2014
DOI: 10.1016/j.ijscr.2014.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Post laminoplasty cervical kyphosis—Case report

Abstract: INTRODUCTIONCervical kyphosis is a progressive cervical sagittal plane deformity that may cause a reduction in the ability to look horizontally, breathing and swallowing difficulties, sense of thoracic oppression and social isolation. Moreover, cervical kyphosis can cause myelopathy due to a direct compression by osteo-articular structures on the spinal cord or to a transitory ischaemic injury. The treatment of choice is surgery. The goals of surgery are: nervous structures decompression, cervical and global s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[2,23] In the past years, it was suggested that hemi-laminectomy or laminotomy with laminoplasty might reduce this complication; results are, however, still controversial. [2,11,14,21,23] In our case, the need for an emergency treatment, combined to the difficulty in "dominating" intraoperative bleeding, led us to "adopt" cervicothoracic "complete" laminectomy, excluding other treatment modalities. Timing of surgery was reported only for two cases.…”
Section: No Other Information Availablementioning
confidence: 85%
“…[2,23] In the past years, it was suggested that hemi-laminectomy or laminotomy with laminoplasty might reduce this complication; results are, however, still controversial. [2,11,14,21,23] In our case, the need for an emergency treatment, combined to the difficulty in "dominating" intraoperative bleeding, led us to "adopt" cervicothoracic "complete" laminectomy, excluding other treatment modalities. Timing of surgery was reported only for two cases.…”
Section: No Other Information Availablementioning
confidence: 85%
“…This can result in a poor horizontal gaze, swallowing and respiratory issues, neck pain, and potential neurological compromise. 9 An anterior approach is often necessary to decompress the spine, realign the cervical vertebrate with hardware insertion, and restore neurological function. 10 In order to ensure the structural integrity of any anterior instrumentation, the use of posterior stabilization has been reported to have better maintenance of sagittal alignment, a higher rate of fusion, and a lower incidence of associated morbidities such as instrument subsidence or adjacent-level disease.…”
Section: Discussionmentioning
confidence: 99%
“…After the introduction of the laminoplasty, many studies reported postoperative kyphotic changes to the cervical spine 2 , 3) . The results of the present study suggest that postoperative cervical spinal deformity is related to poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%